Odinokii golos cheloveka . The Lonely Human Voice - Sokurov, Aleksandr (Lenfilm, 1987)
Poor sound Adaptation of Andrei Platonov's short stories. Red Army soldier comes back to his native town after the Civil war is over. At home he meets his old acquaintance Lyuba, who lives alone. Nikita and Lyuba get married, but their family life is unhappy, as the war took Nikita’s health and strength. Not willing to torture Lyuba, Nikita leaves his town and becomes a vagabond in a city. Learning from an accidental meeting with his father that Lyuba is very ill, he returns.